2021
DOI: 10.5455/msm.2021.33.41-44
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density and Body Fat Distribution in Postmenopausal Women

Abstract: Background: In postmenopause there are changes in metabolism of bone tissue and consequent decrease of bone density. With ageing redistribution of fat occurs and an increase in body weight. Because of hormone changes in postmenopause fat is redistributed from gluteofemoral area to the abdominal region. Objective: The objective of this study was to examine the relationship between bone density and a body mass index (BMI), and distribution of the fat tissue in women in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The body composition results of the current study support the findings of the previous literature discussing the associations of BMD with BMI [7,8], lean mass [9], fat [9], resting metabolic rate (RMR) [9], android fat [10], ratio of trunk fat mass to limb fat mass [11], and relative skeletal muscle index in postmenopausal women [12]. Our study showed significantly higher BMIs in women with greater BMDs (Z-scores ≥ 0) than women with lower BMDs (Z-scores < 0).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The body composition results of the current study support the findings of the previous literature discussing the associations of BMD with BMI [7,8], lean mass [9], fat [9], resting metabolic rate (RMR) [9], android fat [10], ratio of trunk fat mass to limb fat mass [11], and relative skeletal muscle index in postmenopausal women [12]. Our study showed significantly higher BMIs in women with greater BMDs (Z-scores ≥ 0) than women with lower BMDs (Z-scores < 0).…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed significantly higher BMIs in women with greater BMDs (Z-scores ≥ 0) than women with lower BMDs (Z-scores < 0). Similarly, previous studies found a statistically significant positive association between BMI and femur bone density in postmenopausal women [7] and a positive association between BMI and BMD [8]. Additionally, previous reports indicate that BMI may be a contributing factor for BMD, as increased body mass often leads to increased levels of hormones, such as estrone and estradiol, associated with bone building [31].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These findings suggest that the association between serum ALT levels and fat mass may be due to confounding factors. Postmenopausal women are more susceptible to weight gain, loss in body lean mass, and fat redistribution from the gluteofemoral to the abdominal region 13,14 . Furthermore, a previous study showed that women of Chinese origin have a lower fat mass and a higher lean mass than women of South Asian origin 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal women are more susceptible to weight gain, loss in body lean mass, and fat redistribution from the gluteofemoral to the abdominal region. 13,14 Furthermore, a previous study showed that women of Chinese origin have a lower fat mass and a higher lean mass than women of South Asian origin. 15 Finally, significant race difference exists in serum ALT levels.…”
Section: Ta B L E 1 Characteristics Of the Study Participantsmentioning
confidence: 99%